Gestational Weight Gain and Its Effects on Maternal and Neonatal Outcome in Women With Twin Pregnancies: A Systematic Review and Meta-Analysis - Zhong, Wei; Fan, Xiaojiao; Hu, Fang; Chen, Meiqin; Zeng, Fanshu (Frontiers in Pediatrics, 2021)
Background: The incidence of twin pregnancies has risen recently. Such pregnancies are associated with an increased risk for poor maternal and infant outcomes. Gestational weight gain, particularly in singleton pregnancies, has been well-linked with maternal and infant outcomes. The aim of the current meta-analysis was to evaluate the effects of gestational weight gain on maternal and fetal outcomes in women with twin pregnancies. Methods: A systematic search was conducted using the PubMed, Scopus, and Google Scholar databases. Studies, either retrospective or prospective in design, evaluating the effects of gestational weight gain (defined using Institute of Medicine (IOM) guidelines) maternal and/or fetal/neonatal outcomes in women with twin pregnancies were included. Statistical analysis was performed using STATA software. Results: Eleven studies were included in the meta-analysis. Mothers with inadequate weight gain had increased risk for gestational diabetes mellitus (OR 1.19; 95% CI: 1.01, 1.40) and decreased risk for gestational hypertension (OR 0.58; 95% CI: 0.49, 0.68) and cesarean section (OR 0.94; 95% CI: 0.93, 0.96). Neonates born to mothers with inadequate weight gain were susceptible to increased risk for preterm delivery (OR 1.17; 95% CI: 1.03, 1.34), very preterm delivery (gestational age <32 weeks) (OR 1.84; 95% CI: 1.36, 2.48), small for gestational age status (OR 1.41; 95% CI: 1.15, 1.72), low birth weight status (<2500 g) (OR 1.27; 95% CI: 1.17, 1.38), and neonatal intensive care unit (NICU) admission (OR 1.16; 95% CI: 1.08, 1.24). The pooled findings indicate an increased risk for gestational hypertension (OR 1.82; 95% CI: 1.60, 2.06) and cesarean section (OR 1.07; 95% CI: 1.05, 1.08) among mothers with excessive weight gain. Neonates born to mothers with excessive weight gain were susceptible to increased risk for preterm delivery and very preterm delivery, but were associated with a decreased risk for low birth weight status and small for gestational age status. Conclusions: Gestational weight gain in twin pregnancy, either lower or higher than IOM recommended guidelines, is associated with poor maternal and neonatal outcomes. Our findings call for incorporating counselling on optimal weight gain during pregnancy as part of routine antenatal visits.